Analisis Penentuan Pusat Pertumbuhan dalam Pengembangan - Dewi Rahma Amaliya Anggraini; Niniek Imaningsih (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
The purpose of this research is to identify key economic sectors, determine potential sub-districts as growth centers, and analyze inter-regional interactions. This research uses a quantitative research type. The research analysis was conducted using Klassen Typology, Scalogram, and Gravity. The research results show the economic sector, sub-district potential, and inter-sub-district interactions. Sukolilo, Mulyorejo, and Wonokromo sub-districts have been identified as potential growth centers, with significant interactions respectively with Rungkut, Tambaksari, and Wonocolo sub-districts. The establishment of these growth centers is expected to trigger spillover effects that accelerate development in the surrounding areas. This study provides a foundation for sustainable development planning to reduce economic disparities between regions in Surabaya. The conclusion of this study reveals important aspects related to sector development and economic growth potential in Surabaya, a city with diverse sectors such as transportation, finance, education, health, and social services. Keywords: Classification Of Economic Sectors, Interactions Between Sub-Districts, PDRB, Sub-District Potential.